Chronic ulcers and patient management from the perspective of comprehensive health care in multidisciplinary attention: a case report - Elaine Alegre Bueno; Rodrigo de Souza Balk; Odete Messa Torres (Universidade de Santa Cruz do Sul, 2012)
KEYWORKS Family Health, Patient Care Team, Domiciliary consultation